Lymphogranuloma venereum and non-Hodgkin lymphoma: a case report - Passos,Mauro Romero Leal (2012)
Lymphogranuloma venereum (LGV) is an uncommon, contagious, sexually transmitted disease (STD). We report a case of a 17-year-old teenager who presented with a 2-month-old ulcerous vegetant lesion in the right inguinal region. The patient was diagnosed with LGV and received erythromycin treatment. Three months after treatment, he presented with a new ulcerous lesion, very similar to the previous one, in the right supraclavicular region. He was diagnosed with a diffuse large B-cell non-Hodgkin lymphoma. Both diseases are rare in Rio de Janeiro City, Brazil, and physicians should not neglect the possibility of STDs in such cases.